Therapeutic Communication Of "Siraman Qolbu" A discourse perspective - Syifa Fauzia Chairul; Darsita Suparno; Armawati Arbi; Santje Inneke Iroth (International Journal of Linguistics and Discourse Analytics, 2021)
One of the phenomena of social crisis that occurs in society is marked by a trance. Unfortunately, this incident is often associated with mystical aspects. In fact, trance can be explained scientifically and it can be cured through therapeutic communication with religious nuances. This paper attempts to show that the stages of therapeutic communication and speech representation that is performed by Ustadz Danu in the healing process of a possessed person. The main purpose of this study is to develop an understanding of the stages of therapeutic communication and speech representation. This study used a descriptive qualitative approach taking a primary and secondary data sources by observing, documenting, and analysing. The result of this study indicate that: first, there are four stages religious therapeutic communication that can improve the mental peace of trance patients by counsellor through religious activities such as reading salawat, prayers, and dhikr. Second, after getting religious guidance, patients with mental disorders feel more inner peace than before, this can be seen from the patient's independence, and the way of communication of patients who began to gradually improve. Third, utterances of advice that show supporting factors in healing a possessed patient include adequate facilities, infrastructure, and family support